History in primary school textbooks in Portugal: social representations and the construction of identities - Sole, Maria Glória (Historia y Memoria de la Educación, 2017)
The textbook continues to be by far the most widely recognized didactic tool as well the most used by teachers and students in Portugal in the current educational context and in the teaching of history. Textbooks, understood as mediators between programs, historiographical schools, educational policies, normative systems and pedagogical perspectives of teaching, necessarily reflect social representations and in a given context promote the construction of social and political identities. These identities can be more or less homogeneous and are themes that will be discussed in the first part of the text. We intend to analyze social representations (women, men, children, society, etc.), as well as the construction of multiple identities (social, political, cultural) in reading books and textbooks of history in Portugal, within a historical perspective. In our paper, we systematize several studies that have addressed this issue in Portugal. We also present a study in which we analyze and compare reading books and textbooks for teaching history in primary school at different times: there are some texts from the First Republic and others from The Estado Novo (New State), with a greater focus, in this period, on reading books and fourth-year History textbooks. By studying these documents, we seek to identify changes in social representations and in the construction of identities, changes which operate very slowly.